1971
DOI: 10.1021/bi00795a015
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the molecular structure of axonal and red blood cell membranes following treatment with phospholipase A2

Abstract: Phospholipase A2 treatment of erythrocyte membranes resulted in no detectable release of protein and fatty acids, but between 5 and 10% of the lipid phosphorus was released from the membranes. The overall helical configurations of the membrane proteins as determined by circular dichroism measurements appeared unchanged. Investigation

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

1972
1972
1984
1984

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(7 citation statements)
references
References 24 publications
2
5
0
Order By: Relevance
“…are consistent with our previous findings since: 1) phospholipase C is known to produce little perturbation to the lipid bilayer of the membrane [17]; and 2) phospholipase A, while known to cause structural changes in the bilayer [18], probably does not alter its internal dielectric constant. This is supported by previous work which has shown that neither product of hydrolysis, fatty acids or lysolecithin, are removed from the membrane [5,18].…”
Section: Osmium Tetroxide Phospholipases a And Csupporting
confidence: 93%
See 1 more Smart Citation
“…are consistent with our previous findings since: 1) phospholipase C is known to produce little perturbation to the lipid bilayer of the membrane [17]; and 2) phospholipase A, while known to cause structural changes in the bilayer [18], probably does not alter its internal dielectric constant. This is supported by previous work which has shown that neither product of hydrolysis, fatty acids or lysolecithin, are removed from the membrane [5,18].…”
Section: Osmium Tetroxide Phospholipases a And Csupporting
confidence: 93%
“…This is supported by previous work which has shown that neither product of hydrolysis, fatty acids or lysolecithin, are removed from the membrane [5,18]. Thus, the solvent environment surrounding the spin-labeled local anesthetic should be minimally affected.…”
Section: Osmium Tetroxide Phospholipases a And Csupporting
confidence: 58%
“…[Model bilayers composed of phosphatidylcholine, however, are more fluid than those of phosphatidylethanolamine (77,78).] Similar methylation reactions in vesicles of hog kidney cortex did not alter the fluorescence polarization of diphenylhexatriene (130), so the fluidity change may be cell-specific or require special conditions. As noted in a prior section, administration to rats of S-adenosyl-L-methionine, the methyl donor for these transmethylations, increased the fluidity of the hepatocyte plasma membranes isolated subsequently (117).…”
Section: Hepatocyte Plasma Membrane Proteins Influence the Membranementioning
confidence: 99%
“…These changes are ascribed to the action of endogenous phospholipase Az, which is well-known to be calcium-sensitive in the millimolar concentration range (1)(2)(3)(4) and to cleave arachidonate, which is located preferentially at the sn-2 position of the phospholipid backbone (128). Treatment of hepatocyte plasma membranes (129), human erythrocyte membranes (130), or lobster axonal membranes (130) with exogenous phospholipase A2 has also been shown to decrease the lipid fluidity. It is proposed, therefore, that one function of phospholipase Az is as a regulator of membrane fluidity.…”
Section: Hepatocyte Plasma Membrane Proteins Influence the Membranementioning
confidence: 99%
“…and were the 7-nitroxide (n = 10, m= 5) and the 5-nitroxide (n = 12, m = 3). The preparation of these labels has already been described (Simpkins et al, 1971b) except that the 5-oxo acid was prepared as described by Jost et al (1971). The labelling of the membranes with the protein and fatty acid labels was performed as described by Simpkins et al (1971b) except that the buffer employed was 0.5mM-CaC12-1 mM-tris-HCl buffer, pH7.5, and the washing was performed by centrifugation of the membrane fractions at 150000g.…”
Section: Spin-labelling Studiesmentioning
confidence: 99%